The Effect of Social Media Marketing Activities on Brand Loyalty by Examining the Mediating Roles of Brand Trust and Brand Equity at Bank Syariah Indonesia - Gatot Amri; Maya Ariyanti (SMARTINDO, 2025)
Purpose - This study aims to analyze the influence of social media marketing activities on brand loyalty, by considering the mediating roles of brand trust and brand equity at Bank Syariah Indonesia. The research is motivated by the phenomenon of declining brand loyalty at BSI, as evidenced by fluctuations in customer loyalty and a downward trend, particularly in the collection of third-party funds under the Wadiah scheme. Design/methodology/approach - A quantitative approach was employed using a survey method, with questionnaires distributed to 342 active BSI customers. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS) to assess the relationships among the variables. Originality - The results indicate that social media marketing activities do not have a significant direct effect on brand loyalty. However, they significantly influence brand trust and brand equity, which in turn enhance brand loyalty. Moreover, brand trust and brand equity were found to play strong mediating roles in strengthening the impact of social media activities on brand loyalty. Findings and Discussion - These findings indicate that effective social media management can be a key strategy in building long-term relationships with customers while enhancing trust and brand value for BSI in the Islamic banking market, both nationally and globally. Conclusion - This study also contributes theoretically to the field of digital marketing and provides practical recommendations for the development of communication strategies in Islamic banking specifically, as well as for businesses in general. Purpose - This study aims to analyze the influence of social media marketing activities on brand loyalty, by considering the mediating roles of brand trust and brand equity at Bank Syariah Indonesia. The research is motivated by the phenomenon of declining brand loyalty at BSI, as evidenced by fluctuations in customer loyalty and a downward trend, particularly in the collection of third-party funds under the Wadiah scheme. Design/methodology/approach - A quantitative approach was employed using a survey method, with questionnaires distributed to 342 active BSI customers. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS) to assess the relationships among the variables. Originality - The results indicate that social media marketing activities do not have a significant direct effect on brand loyalty. However, they significantly influence brand trust and brand equity, which in turn enhance brand loyalty. Moreover, brand trust and brand equity were found to play strong mediating roles in strengthening the impact of social media activities on brand loyalty. Findings and Discussion - These findings indicate that effective social media management can be a key strategy in building long-term relationships with customers while enhancing trust and brand value for BSI in the Islamic banking market, both nationally and globally. Conclusion - This study also contributes theoretically to the field of digital marketing and provides practical recommendations for the development of communication strategies in Islamic banking specifically, as well as for businesses in general.